Relasi Agensi dan Struktur: Komparasi Interaksi Negara dengan Pers pada Era Orde Baru dan Reformasi - Hardi, Lalu Ary Kurniawan (Jurnal Analisis Sosial Politik, 2023)
The interaction between the state and the press commonly assessed using a functional-structural approach which assumed political subjects as a rigid element of political structure, because they act based on assigned roles. As a critique of this view, Anthony Giddens with his structuration theory perceived the state and the press as the agencies that have an active discretion in their position towards the structure. This freedom then provides more accessibility for an agency to control the existing structure–rather than being subject to the role given to it by the structure. This article written to fill the academic gap in the study of the relationship between the state and the press by emphasizing the main premise of Anthony Giddens’ structuration theory and the comparative-historical approach (CHA) to examine the causality of agency circulation in Indonesia. I argue that in the context of the New Order Regime, the press was positioned as a passive actor, the state as a structure, and the regime as an agency. In the context of the reform era, the press was transformed into a political agency in Indonesia along with the existing regime. This is corollary related with the expansion of power into the media sphere. This article draws a general conclusion that even though press freedom can be achieved, rules regarding press credibility should be enforced in order to avoid politicization of the media due to the position of the political agency owned by the press and the regime which exist at the same level.